Chinas Move to Preferential Trading: An Extension of Chinese Network Power? - Xang Jiang; John Ravenhill (Copenhagen Business School (CBS), Asia Research Centre (ARC), 2007)
China is a latecomer to preferential trading agreements (PTAs), choosing to complete its accession to the WTO before embarking on negotiations for preferential agreements. Since 2001, China has become a very active player in such agreements, currently having concluded treaties or being in the process of negotiating them with close to 30 partners. China's approach to PTAs is characterized by pragmatism; rather than following the American and European practices of using a template for all partnerships, China has been willing to tailor agreements to the specific relationships it is pursuing. Like other governments, China has a mixture of motives in pursuing PTAs. In some relationships, diplomatic/strategic considerations are paramount. In others, China seeks to pursue various economic interests, one of the most significant of which has been security of supply of raw materials. China's various motivations in PTAs are examined through three case studies: the Closer Economic Partnership Agreement with Hong Kong; the China-ASEAN Free Trade Area; and the negotiation of a PTA with Australia.
hdl:10398/7414
Keywords: 330